A Quantitative Arabidopsis IRE1a Ribonuclease-Dependent in vitro mRNA Cleavage Assay for Functional Studies of Substrate Splicing and Decay Activities - Diwan, Danish; Liu, Xiaoyu; Andrews, Caroline F.; Pajerowska-Mukhtar, Karolina M. (Frontiers in Plant Science, 2021)
The Unfolded Protein Response (UPR) is an adaptive eukaryotic reaction that controls the protein folding capacities of the endoplasmic reticulum (ER). The most ancient and well-conserved component of the UPR is Inositol-Requiring Enzyme 1 (IRE1). Arabidopsis IRE1a (AtIRE1) is a transmembrane sensor of ER stress equipped with dual protein kinase and ribonuclease (RNase) activities, encoded by its C-terminal domain. In response to both physiological stresses and pathological perturbations, AtIRE1a directly cleaves bZIP60 (basic leucine zipper 60) mRNA. Here, we developed a quantitative in vitro cleavage assay that combines recombinant AtIRE1a protein that is expressed in Nicotiana benthamiana and total RNA isolated from Arabidopsis leaves. Wild-type AtIRE1a as well as its variants containing point mutations in the kinase or RNase domains that modify its cleavage activity were employed to demonstrate their contributions to cleavage activity levels. We show that, when exposed to total RNA in vitro, the AtIRE1a protein cleaves bZIP60 mRNA. Depletion of the bZIP60 transcript in the reaction mixture can be precisely quantified by a qRT-PCR-mediated assay. This method facilitates the functional studies of novel plant IRE1 variants by allowing to quickly and precisely assess the effects of protein mutations on the substrate mRNA cleavage activity before advancing to more laborious, stable transgenic approaches in planta. Moreover, this method is readily adaptable to other plant IRE1 paralogs and orthologs, and can also be employed to test additional novel mRNA substrates of plant IRE1, such as transcripts undergoing degradation through the process of regulated IRE1-dependent decay (RIDD). Finally, this method can also be modified and expanded to functional testing of IRE1 interactors and inhibitors, as well as for studies on the molecular evolution of IRE1 and its substrates, providing additional insights into the mechanistic underpinnings of IRE1-mediated ER stress homeostasis in plant tissues.